SPIRITUAL LEADERSHIP: LITERATURE REVIEW AND CONTENT ANALYSIS (Third Sector Social Economic Review, 2022)
Spiritual leadership is a process that intrinsically motivates both the spiritual leader and her/his followers in a spiritual atmosphere to achieve positive results at the individual, group and organizational levels. Given some information about the spiritual leadership’s scale, dimensions, antecedent and outcome variables in the studies carried out by Fry alone or with his friends between 2003 and 2017 has been transferred to the national literature in a different way from the original studies. This situation has led to many contradictions in the national literature. This study aims to eliminate the problems in the national literature and to give direction to it by giving detailed information about the relevant issues in the “literature review” section. In addition, this study reveals the current status and trend of graduate theses written in Turkey on the subject of spiritual leadership. Thus, this study also aims to shed light on the researchers who are considering working on this subject. For this purpose, the Database of National Thesis Center of the Council of Higher Education was searched until 2021. As a result of the search, a total of twenty-two graduate theses prepared between 2009 and 2021, of which are fifteen master’s theses, six doctoral dissertations and one “specialization in medicine” thesis with determinations/inferences and/or findings about spiritual leadership, were included in the research scope of this study. And then, content analysis was employed by using secondary data to determine the bibliometric characteristics of these theses in terms of “descriptive features”, “content and research method”, “sample”, “data”, “analysis techniques”, “references” and “citation”. The findings of analysis were tabulated mostly on the basis of frequency and percentage in terms of the type of thesis, in line with the research questions and criteria determined. Based on these findings, determinations/inferences and suggestions for future studies were made in the “discussion and conclusion” section.
Keywords: Spiritual Leader(ship); Content Analysis; Bibliometric Analysis; (Graduate) Thesis